Using Partial Credit Model to Improve the Quality of an Instrument - Saras Krishnan; Noraini Idris (Institute of Advanced Engineering and Science, 2018)
In using the Rasch model to improve the quality of an instrument, analysis purports to determine if the sample collaborates well with the items in the instrument such that the results are measuring a single underlying variable. The relevant properties of Rasch analysis are reliability and validity which are key indicators of the quality of a measurement instrument. This paper discusses the use of one type of Rasch model that is the Partial Credit Model to investigate reliability and validity of an instrument. By removing or changing items in the instrument when conditions of reliability and validity are not met, the quality of the instrument is improved.